TINGKAT KEMAMPUAN DESA DALAM MELAPORKAN LAPORAN PERTANGGUNGJAWABAN PENGGUNAAN DANA DESA DI KECAMATAN DELIMA KABUPATEN PIDIE - Maisur Maisur; Cut Hamdiah (Jurnal Sains Riset, 2022)
The purpose of this study was to see the level of village capacity in reporting accountability reports on the use of village funds in the Delima sub-district, Pidie district. The sample in this study were 44 financial groups. In determining the sample using saturated sampling and field research methods. While the analytical tool used is multiple linear regression. From the results of the analysis, it is found that the village's ability to report accountability reports is dominated by HR factors on educational background indicators, information technology on application update indicators, supporting facilities on internet indicators, internal control systems on multiple positions indicators, and the rule of law on minimal indicators. understanding of laws and regulations. The implication of this research for the working unit is that it can improve the quality of timely submission of financial reports.Keywords : Financial Reports, Human Resources, Information Technology